Can Cash Management System Reduce Fraud Indications in Government Transactions? - Anggia, Sofina; Mutmainah, Siti (International Journal of Science and Society, 2025)
This research aims to see the role of the Cash Management System (CMS) components in facilitating government non-cash transactions, so as to reduce fraudulent behavior such as asset missapropriation, corruption and financial statement fraud. Primary data was collected using a questionnaire. A sample of 266 were selected randomly, who were active expenditure treasurers at the BPS- Statistics Indonesia from various regions in Indonesia. Data analysis uses SEM-PLS with the 2nd Order model and shows the negative influence of CMS effectiveness on government non-cash transactions to indications of fraud. CMS components such as human resources, procedures and instructions, IT infrastructure and systems, data, and internal control have generally been running well. In the future, services need to be improved in providing information and procedures as well as the performance of the CMS application system. The role of vendors is also very important in providing non-cash payment modes, so that this payment mode becomes a priority. There are not many studies that specifically discuss CMS as a non-cash payment method, previous research is qualitative methode. Previous government non-cash transaction research used regency-wide samples, for this reason this research expands the sample to a national scope.